2019
DOI: 10.1016/j.jsxm.2019.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Daily Oral l-Arginine Plus Tadalafil in Diabetic Patients with Erectile Dysfunction: A Double-Blinded, Randomized, Controlled Clinical Trial

Abstract: Introduction Erectile dysfunction is a common condition among diabetic men. Many treatments are now available with variable responses. Aim This study aimed to evaluate the effect of daily oral l-arginine plus tadalafil in diabetic patients with mild to moderate erectile dysfunction. Methods A double-blinded, randomized, controlled clinical trial was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Due to the lack of useful data, 61 studies were excluded. Four RCTs (Abu El‐Hamd & Hegazy, 2020; El Taieb et al., 2019; El‐Wakeel et al., 2020; Gallo et al., 2020) including 373 patients were used to access the effect and safety of daily oral L‐arginine and PDE5Is alone or combination in treating patients with ED. A selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the lack of useful data, 61 studies were excluded. Four RCTs (Abu El‐Hamd & Hegazy, 2020; El Taieb et al., 2019; El‐Wakeel et al., 2020; Gallo et al., 2020) including 373 patients were used to access the effect and safety of daily oral L‐arginine and PDE5Is alone or combination in treating patients with ED. A selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The above results are consistent with the results of previous research. One RCT found that compared with L‐arginine or tadalafil alone, daily oral L‐arginine and tadalafil significantly improved the IIEF score and total testosterone levels in patients with diabetic ED (El Taieb et al., 2019). Another RCT reported that compared with sildenafil alone, IIEF scores of the combination of L‐arginine and sildenafil daily group were significantly increased in patients with ED (Gallo et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In l-ARG group, at T1, IIEF-6 score was significantly increased compared to T0 [24 (19-25.3) vs 20 (16)(17)(18)(19)(20)(21)(22); p < 0.0001] (Fig. 2).…”
Section: Iief-6 Questionnairementioning
confidence: 94%
“…Moreover, the combination of L-arginine with a phosphodiesterase type 5 inhibitor (e.g., tadalafil) is more effective in improving erectile function in men [14,15]. Daily intake of L-arginine with tadalafil significantly increased the IIEF 5-item questionnaire scores, and total testosterone levels compared to single dose of each medication in diabetic patients with ED [16]. The normal range of L-arginine plasma levels has been specified as 81.6 ± 7.3 mmol/L in young men and 113.7 ± 19.8 μmol/L in elderly men [17].…”
Section: L-arginine Deficiency and Male Erectile Dysfunctionmentioning
confidence: 99%